Predicting the Future of Halal Industry through Search Engine Analytics: A Maqashid Shariah Framework - Asep Koswara; Anisa Nurbilla (International Journal of Islamic Finance, 2026)
Background: The global halal industry has transformed from a faith-based sector into a dynamic, multi-sectoral market encompassing food, cosmetics, tourism, and Islamic finance. Rapid digitalization and online consumer behavior have reshaped market demand, yet most analyses remain descriptive, overlooking predictive insights and ethical evaluation through Islamic economic frameworks.  Objectives: This study aims to predict future trends in the global halal industry from 2026 to 2030 by analyzing search engine data (2020–2025) within a Maqashid Shariah framework. It seeks to bridge digital consumer behavior with Islamic economic values and sustainability, providing evidence-based foresight across halal sectors.  Novelty: This research pioneers the integration of search engine analytics and Maqashid Shariah as a predictive framework, filling gaps in the literature where empirical digital trends are rarely interpreted through Shariah objectives. It uniquely combines time-series forecasting with ethical evaluation to inform strategic decision-making in the halal economy.  Research Methodology / Design: A mixed-methods approach was applied. Quantitative analysis utilized Google Trends to capture global search interest in “halal food,” “halal cosmetics,” “halal tourism,” and “Islamic finance” from 2020–2025. Time-series forecasting models (ARIMA and Prophet) projected trends to 2030. Rising and breakout keyword analyses identified emerging consumer intentions. Qualitative interpretation employed a Maqashid Shariah–based analytical lens to connect digital patterns with Islamic ethical principles for ensuring coherence between empirical signals and value-driven interpretation.  Findings: The study finds that global interest in the halal industry continues to strengthen across all major sectors, driven by rising digital engagement and increasingly value-driven consumer intentions. Search behavior shows a shift from basic informational queries toward action-oriented, trust-seeking, and ethically motivated searches. Each sector including food, tourism, cosmetics, and Islamic finance demonstrate distinct post-pandemic recovery patterns and growing recognition of halal as a global ethical standard. Predictive modeling indicates continued expansion and deeper cross-sector reinforcement, where growth in one segment amplifies interest in others. Interpreted through a Maqashid Shariah lens, these trends align with human well-being, ethical consumption, responsible finance, and sustainability.  Implication: Findings provide actionable insights for policymakers, halal certification authorities, and entrepreneurs to align governance, strategy, and innovation with both consumer behavior and Shariah-based sustainability.